Sexual Expression in Alberta's Continuing Care Homes: Capacity, Consent, and Co-decision-making. Issue 1 (24th March 2021) - Brassolotto, Julia; Howard, Lisa; Manduca-Barone, Alessandro
ABSTRACT: In this article, we explore the role of substitute decision-makers (SDMs) in matters of sexual expression for continuing care residents with diminished cognitive capacity. We examine how Alberta's current use of SDMs can enable an "all-or-none" approach to competence, wherein a person either has capacity to make all decisions or is incapable of making any. Three factors facilitate an environment in which this approach can influence residents' sexual expression. These include the wording of current legislation, lack of resources for SDMs, and relational dynamics between SDMs and care staff. We provide a critical review of existing legislation and empirical evidence of its challenges in practice. Though we focus on the Alberta context, there is reason to believe that similar issues persist in other Western jurisdictions. We offer several recommendations for how we can better support residents' sexual autonomy in continuing care and avoid pitfalls of the "all-or-none" approach to competence.